Realizem maturitetnega eseja - Krakar-Vogel, Boža (Jezik in slovstvo, 1999)
The concept of the matura essay in Slovenia is presented, based on the contemporary aims of teaching literature and the situation in schools. It is compared to solutions in several other systems of knowledge testing. Similarities and informed differences are discussed, as well as possible forthcoming changes in essay writing resulting from analyses and observations done so far from the renovated curriculum for teaching literature at grammar schools.
Keywords: Slovene literature; slovenska književnost; pouk književnosti; eseji; matura